Negentropy for the anthropocene; Stiegler, Maori and exosomatic memory. Issue 5 (16th April 2022) - Irwin, Ruth; White, Te Haumoana
Abstract: Exosomatic memory is a crucial phase in the evolution of humanity because it enables learning to take place across groups and generations rather than exclusively through lived experience or one on one transmission. Exosomatic memory is the attribution of knowledge to objects, such as art or writing, which allows epistemology to be transmitted beyond the individual to subsequent generations of people. Exosomatic memory is the key to the transmission of culture and knowledge, beyond the individual who learns exclusively from personal experience. This places technologies such as writing and art in a key position for the education of culture and knowledge. Stiegler develops these ideas, following Martin Heidegger, Leroi-Gourhan and Derrida from the Palaeolithic to the contemporary. Maori use of natural objects as exosomatic transmission of intergenerational learning exceeds the technological enframing of modernity outlined by Heidegger. For indigenous peoples, exosomatic memory is cultural, technological and ecological. Stiegler argues that the impact of cybernetics on knowledge production is accelerating the technological enframing of knowledge (2018). Consequently, information technologies are leaving the human mind behind, in passive receptivity rather than dynamic creativity. The prefrontal cortex is slower than the internet, exacerbating a widening lag in active understanding, in favour of passive absorption. Alienation and epistemological entropy are trapping us in climate change and the anthropocentric Capitalocene. Maori insight may cut the Gordian knot and sidestep the alienation and determinism of technological modernity.